2006
DOI: 10.1021/ie0607393
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Critical Properties and Surface Tensions for n-Alkanes by Perturbed-Chain Statistical Associating Fluid Theory Combined with Density-Gradient Theory and Renormalization-Group Theory

Abstract: The perturbed-chain statistical associating fluid theory (PC−SAFT) and density-gradient theory (DGT) are used to construct an equation of state (EOS) applicable for nonuniform fluids. In the bulk phases, the nonuniform EOS reduces to PC−SAFT and the phase equilibria inside the critical region are calculated by combining the renormalization-group theory (RGT). In the vapor−liquid surface, the density profile, surface thickness, and surface tension are calculated by using the nonuniform EOS with the equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 49 publications
1
58
0
Order By: Relevance
“…In usual implementations of the RG relations in SAFT approaches 53,54,[59][60][61] , equations (26) and (27) are expressed asf…”
Section: B Usual Implementation In Saft Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…In usual implementations of the RG relations in SAFT approaches 53,54,[59][60][61] , equations (26) and (27) are expressed asf…”
Section: B Usual Implementation In Saft Approachesmentioning
confidence: 99%
“…However, in these other works 48,49,[51][52][53][54][59][60][61] , the cutoff length L has a slightly different meaning: it instead separates the classic (mean-field) part of the free energy and the non-classic (critical)…”
Section: B Usual Implementation In Saft Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, the Helmholtz energy density can be described from any equation of state (EoS), with the consequence that a single EoS can be used to predict both phase equilibrium and interfacial properties. Previous works demonstrated that the combination of the SGT with cubic type EoS [6][7][8][20][21][22][23][24][25][26][27] as well as molecular based EoS [9,[28][29][30][31][32][33] models is promising for correlating and/or predicting interfacial properties in some pure hydrocarbon and hydrocarbon mixtures in a wide range of temperatures, pressures and concentrations. Both the SGT and available EoS models require at some stage experimental data for pure component parameter fitting.…”
Section: Theorymentioning
confidence: 99%
“…SGT and SAFT are well known, and only the equations that are central to this work will be recalled in this section. In spite of this, it is noteworthy that only a few papers are devoted to use SGT approach with the SAFT EoS for the hydrocarbon mixtures [9,[30][31][32][33].…”
Section: Theorymentioning
confidence: 99%